Conflict, Mobilization, and Deindustrialization: The 1980 Gardner Strike and Occupation. Issue 37 (September 2016) - Mustchin, Stephen
Abstract : The diesel engine manufacturer L. Gardner and Sons saw two long strikes in 1968 and late 1972, after which a militant shop-steward leadership emerged. In 1980 a high-profile strike and occupation against mass redundancies at the height of the manufacturing recession won significant concessions. The organization exhibited by the Gardner workforce was remarkable and represented a partial victory in a period when strikes were declining and increasingly difficult to organize. However, a countermobilization by the company led to the erosion of the gains: established practices based on 'mutuality' (where working times and work organization were agreed between unions and management) were eroded, with managerial control reasserted through regular redundancies. The erosion of the concessions won by the 1980 strike and occupation demonstrates the fragility of gains achieved through trade-unionism. It also demonstrates the difficulty of maintaining strong workplace organization in the face of recession, deindustrialization and counter-mobilization by employers and the state in Britain in the 1980s.